Annotated translation and subtitling of the documentary "Waste Deep". - Álava Intriago, Yordy Arón (2018)
The present project provides an annotated translation and subtitling of a documentary whose aim is to boost awareness of environmental issues and serves as a tool of knowledge and change. The audio-visual information breaks down the topic of environmental pollution and focuses on waste found in many forms such as food and recyclable materials, and industries like food packaging industries and fashion. The documentary “Waste Deep,” produced in Australia, tells the story of people from different walks of life trying to make a difference with their different projects and movements, aiming to lessen the current environmental crisis and demonstrating how every individual can make an impact, either positive or negative, in the planet by their day-to-day activities, as well as how easy it is to become an environmental activist. The documentary is found only in English, and the information it provides is very rare to be produced accurately in Hispanic regions.